(3CeGdj GdTLQjs - (3jMji Hf GdMSjf Hf ESeGYjd GdTLQj, CHh GdMSf, GdeQTO HGddg , J (B479 (3g` s ((3ehSi Hf eMeO Hf Ydi Hf jYjT s)
(3ChdgG (B:s
(3eLdS ai PcQ GdehJ hgh GdKGdK hGdeGFI s
(3BNQgG (B:s
(3eLdS ai PcQ Gddg JYGdi hgPG GdeLdS GdKeGfjI hGdKdGKjf hGdeGFJjf s
(3HjJOi ef GdeLdS (B103 (3Edi GdeLdS (B60 (3GJe eLGdS CNQi hHChdg agQSs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs